Surgery for metastases, anatomical and ethical limits : Special aspect: oligometastases - Perrakis, Aristotelis; Juratli, T. A.; Hohenberger, Werner; Croner, R. S.; Schackert, G. (Chirurg, 2016)
The surgical resection of metastases is nowadays feasible in selected patients with multifocal metastatic disease due to the implementation of interdisciplinary multimodal therapeutic options. Anatomical limitations do not seem to represent obstacles which cannot be overcome because of the development of new surgical techniques. The cornerstone of the selection of patients is the correct staging diagnosis achieved through modern diagnostic tools; however, surgery alone does not always offer acceptable survival and recurrence-free rates. Furthermore, in every complex surgical procedure there is the risk of morbidity and mortality; therefore, parameters such as alternative therapeutic modalities, the individual situation of the patient and tumor biology have to be considered in order to make the correct selection of patients. This is one of the major future challenges and should never be driven by unfounded hopes and expectations of the patients. The same principle also applies for brain metastases, which represent the most common brain tumors. Approximately 70 % of patients with brain metastases have 1-3 lesions (oligometastases). Treatment is now individualized and the goal of therapy has shifted towards long-term survival (>= 24 months) and improved quality of life. Under this aspect surgery is one of the important treatment options, particularly in patients with a single metastasis or oligometastases. Furthermore, approximately 20 % of patients who have recurrent brain metastases, successfully undergo a complete resection of tumors and with a Karnofsky performance status (KPS) score > 70 show a long-term survival of >= 24 months.
EVALuna2:15224